To Innovate or Not to Innovate: Faculty Willingness and Reluctance to Integrate Generative AI in Higher Education - Louis Nadelson; Brandy Walthall; Janet Filer; Evan W. Faidley (PT. Academic Bright Collaboration, 2026)
Purpose – To investigate how U.S. tertiary faculty perceive and integrate generative artificial intelligence (GenAI) in teaching, ethical communication, and professional practice, addressing gaps in cross-institutional U.S.-based, theory-driven, and rural-inclusive faculty research.Design/methods/approach – Guided by Rogers’ (2003) diffusion of innovations theory, an exploratory cross-sectional mixed-methods online survey (N = 131; Cronbach’s α = .90) combined 20 Likert items with 5 open-ended prompts, analyzed through descriptive and inferential statistics and descriptive content analysis.Findings – Faculty engagement was bifurcated. A committed minority adopted GenAI for planning, differentiation, and assessment, while a larger group used it minimally. Participants endorsed ethical dialogue and disclosure expectations (Mdns = 4.0 and 5.0) yet voiced concern that GenAI diminishes critical thinking (Mdn = 4.0). Significant differences emerged by gender, discipline, and institutional locale, rural faculty expressed greater concern and lower preparation than suburban peers, but not by age or tenure.Research implications/limitations – The cross-sectional design, a self-selected, predominantly female and Caucasian sample, and small sample size constrain generalizability; AI literacy was not directly measured; however, findings support co-construction of GenAI policies with faculty and students, targeted professional development for rural faculty, and integration of AI literacy into curricula.Originality/value – This study offers the first U.S. cross-institutional, theory-driven account of tertiary faculty GenAI engagement and a debut to comparing rural and suburban institutions, providing a baseline for longitudinal, equity-based research and recommendations for policy, faculty development, and pedagogy.